The Influence of Fear of Missing Out and Self-Control on Zuhud Values among Adolescents in Islamic Education - Nuita Alifia Hasanah; Minan Ainur Fatah; Irfan Musonif; Ifada Novikasari (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The rise of digitally mediated consumer culture has intensified concerns regarding adolescents’ moral-spiritual resilience, particularly within highly visual social media environments that continuously promote symbolic consumption and lifestyle comparison. Unlike previous Fear of Missing Out (FoMO) studies predominantly focused on psychopathological outcomes and problematic technology use, this study examines FoMO within the framework of moral-spiritual development and Islamic ethical values. The study aimed to analyze the relationships between social media fashion-related FoMO, self-control, and students’ zuhud values in Islamic junior secondary education. A quantitative correlational design was employed involving 70 eighth-grade students of MTs Ma’arif NU 2 Cilongok selected through simple random sampling. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression. The findings revealed that FoMO fashion did not significantly predict students’ zuhud values (B = 0.086, p = .238), whereas self-control demonstrated a positive and significant effect (B = 0.580, p < .001). Simultaneously, both variables explained 46.7% of the variance in zuhud values (R² = .467; F = 20.60, p < .001). The findings challenge technologically deterministic assumptions that social media exposure inevitably weakens adolescent morality and position zuhud as a form of spiritual self-regulation relevant to strengthening adolescents’ moral resilience within contemporary digital culture.